Prospective associations between peer teasing in childhood and young men's obesity. Issue 6 (November 2017) - Kerr, David C.R.; Gini, Gianluca
Highlights: Research indicates children with obesity are more often teased and bullied than other children. The longterm negative consequences of bullying have been documented for psychosocial outcomes. Negative effects of peer teasing on adult obesity risk has not been consistently supported. In the present study, being teased by peers at ages 10–12 years did not prospectively predict young men's BMI or obesity. Summary: Objective: Being teased and otherwise victimised by peers during childhood increases risk for obesity. However, few prospective studies have considered whether risk extends to adulthood. We tested whether being teased in childhood predicted higher body mass index (BMI) and increased odds of obesity in early adulthood in a community sample of American males. Method: Boys ( n  = 206) were classified as victims of peer teasing or non-victims ( n   =  55 and 151, respectively) based on mother, father, and teacher reports at ages 10–12 years. BMI was assessed at ages 24 or 32 years for 203 of the participants. Family income, parent and child depressive symptoms, child antisocial behaviour, and childhood BMI were assessed at ages 10–13 years and served as control variables. Results: In unadjusted comparisons, childhood victims did not differ significantly from non‐victims on BMI (mean [ SD ] = 27.49 [4.53] and 26.97 [4.60], respectively) or rates of obesity (42% and 31%, respectively) in early adulthood. In adjusted models, no group differences emerged for BMI ( β [95% confidence interval ( CI )] = .02 [−.09 to .13], p  = .77) or obesity (odds ratio [95% CI] = 1.58 [.67–3.71], p  = .30). Conclusions: Peer victimization has been associated with immediate and long-term maladjustment outcomes that are in some cases life threatening. However, our null results do not support that peer victimization significantly increases long-term risk for obesity, and findings are consistent with two other long-term prospective studies of this issue.